STUDENTS’ DIFFICULTIES IN SPEAKING ENGLISHAT THE ELEVENTH GRADE OF SMK NEGERI 2 SIDUAORI - Hia, Buala Zatulo; Laia, Mohamad Yunus (Universitas Nias Raya, 2024)
The objectives of this research were to find out the types of students' difficulties in speaking English at the eleventh grade TKJ of SMK Negeri 2 Siduaori and to explain the factors Students' difficulties in Speaking English to Eleventh grade TKJ of SMK Negeri 2 Siduaori. This research was applied in qualitative research design and the data were obtained through the classroom observation and interviews. The data were analyzed by using Miles and Huberman theory such as data reduction, data display and conclusion drawing and verification. The result of this study showed that the students at the Eleventh grade TKJ of SMK Negeri 2 Siduaori were experienced the students' difficulties in speaking English they are pronunciation, vocabulary, grammar, fluency and comprehension. The factors that to the students' difficulties in Speaking English such as speaking in front of the class, being called by the teacher, incomprehensible input or unclear explanation, being ridiculed by peers/classmates, appropriate teaching method, low self-esteem, lack of vocabulary, lack of pronunciation, lack of grammar, lack of fluency and lack of comprehension and the students' beliefs about learning English, English is excessive, and stressful learning experience. The researcher figured out that the sources of these factors are not only come from the teacher but also from the students. This research showed that the teacher's awareness of the students' difficulties in speaking English is insufficient. Thus, it is extremely important to increase teacher's awareness since speaking is the main factor which affects the students' learning Knowing the students' speaking on English learning will absolutely influence the teacher in treating the students properly. The students should respect each other and support each other in growing together and developing skills in the class.